2018
DOI: 10.1101/365841
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptation of human iPSC-derived cardiomyocytes to tyrosine kinase inhibitors reduces acute cardiotoxicity via metabolic reprogramming

Abstract: Tyrosine kinase inhibitors (TKIs) are widely used to treat solid tumors but can be cardiotoxic.The molecular basis for this toxicity and its relationship to therapeutic mechanisms remain unclear; we therefore undertook a systems-level analysis of human cardiomyocytes exposed to four TKIs. Cardiomyocytes (CMs) differentiated from human induced pluripotent stem cells (hiPSCs) were exposed to sunitinib, sorafenib, lapatinib or erlotinib and responses assessed by functional assays, microscopy, RNA sequencing and m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Cardiotoxicity is typically defined as toxicity that adversely affects the heart and may eventually lead to cardiomyopathy [2]. A variety of anticancer drugs, such as immune checkpoint inhibitors (ICIs), TKIs [3], proteasome inhibitors [4], and microtubule inhibitors [5], have shown to exert harmful effects on the cardiovascular system through their own toxic effects or increasing the side effects of other drugs [6]. Moreover, some of them [7] could induce life-threatening cardiotoxicity such as ischemia, infarction, arrhythmia, and damage to cardiac valves, the conduction system, or the pericardium [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiotoxicity is typically defined as toxicity that adversely affects the heart and may eventually lead to cardiomyopathy [2]. A variety of anticancer drugs, such as immune checkpoint inhibitors (ICIs), TKIs [3], proteasome inhibitors [4], and microtubule inhibitors [5], have shown to exert harmful effects on the cardiovascular system through their own toxic effects or increasing the side effects of other drugs [6]. Moreover, some of them [7] could induce life-threatening cardiotoxicity such as ischemia, infarction, arrhythmia, and damage to cardiac valves, the conduction system, or the pericardium [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, determining the optimal dose of this drug in patients with a-DCM will be the key to maximize the clinical benefits and reduce the side effects. Previous TKI toxicity studies using iPSC-CMs, iPSC-endothelial cells, and iPSC-cardiac fibroblasts have shown that TKIs in general are toxic at concentrations higher than 1 ÎĽM ( 69 , 70 ). On the basis of our findings, 1 ÎĽM crenolanib conferred cardiac function improvement without compromising cardiomyocyte survival (fig.…”
Section: Discussionmentioning
confidence: 99%
“…The highest magnitude of cardiotoxicity observed was induced by the VEGFR2/PDGFR-inhibiting TKIs. In a related study, Wang et al [ 162 ] assessed iPSC-CMs response to four widely administered TKIs (sunitinib, sorafenib, lapatinib and erlotinib), using functional assays, microscopy, RNA sequencing and mass spectrometry. In general, the TKIs affected tyrosine kinase-mediated signal transduction and cardiac metabolism.…”
Section: The Use Of Ipsc-cms For Disease Modeling and Developing Nmentioning
confidence: 99%